2016
DOI: 10.3171/2016.5.focus16169
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of aggressive vertebral hemangiomas

Abstract: OBJECTIVE Vertebral hemangiomas are common tumors that are benign and generally asymptomatic. Occasionally these lesions can exhibit aggressive features such as bony expansion and erosion into the epidural space resulting in neurological symptoms. Surgery is often recommended in these cases, especially if symptoms are severe or rapidly progressive. Some surgeons perform decompression alone, others perform gross-total resection, while others perform en bloc resection.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
53
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 65 publications
(80 reference statements)
1
53
0
6
Order By: Relevance
“…Surgical therapy is still the most radical method of clinical treatment of aggressive VHs. The surgical procedures mainly involved laminectomy decompression, intralesional vertebrectomy, and en-bloc spondylectomy; butthe formulation of ideal surgery for treating these lesions is still a matter of debate because of the rarity ofaggressive VHs [4,6,7,17].In this study, we reported 6 patients with compression fracture caused by aggressive VHs. These patients were treated with our modi ed multimodality surgery (preoperative embolization, intraoperative injection of gelfoam mixed with bone cement combined laminectomy decompression).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Surgical therapy is still the most radical method of clinical treatment of aggressive VHs. The surgical procedures mainly involved laminectomy decompression, intralesional vertebrectomy, and en-bloc spondylectomy; butthe formulation of ideal surgery for treating these lesions is still a matter of debate because of the rarity ofaggressive VHs [4,6,7,17].In this study, we reported 6 patients with compression fracture caused by aggressive VHs. These patients were treated with our modi ed multimodality surgery (preoperative embolization, intraoperative injection of gelfoam mixed with bone cement combined laminectomy decompression).…”
Section: Introductionmentioning
confidence: 92%
“…For asymptomatic VHs, treatment is unnecessary. However, in rare instances, VHs can present as a locally aggressive behave way by enlarging and extending into the spinal canal and/or paravertebral space, leading to spinal cord compression [3][4][5][6]. Aggressive VHs oftenexhibit several symptoms, including local back pain, radicular pain, or even neurological de cits.…”
Section: Introductionmentioning
confidence: 99%
“…Vertebral hemangioma is a rare, benign vascular tumor of the vertebral body that is usually asymptomatic, but which can behave in a locally aggressive way by involving bone and local spread into the vertebral canal to cause spinal cord compression. Between 0.9–1.2% of vertebral hemangiomas are aggressive, or symptomatic [ 1 6 ], with aggressive vertebral hemangioma extending into the spinal canal and/or paravertebral space, leading to neurological deficit [ 2 , 4 , 7 12 ]. The choice of treatment for aggressive vertebral hemangioma is controversial, and in the literature, most previous reports have focussed on surgical management [ 2 , 4 , 7 , 8 , 11 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Декомпрессивно-стабилизирующее вме-шательство с интраоперационной открытой вертебропластикой пораженного позвонка является безопасным и эффективным методом лечения агрессивной гемангиомы позвонка типа IIIB. В 2016 г. Vasudeva et al [41] опубликовали данные о хирургическом лечении агрессивных гемангиом IIIВ типа. В 80 % случаев после операции неврологическая симптоматика регрессировала.…”
Section: Discussionunclassified